Neither here nor there : travels in Europe - Bryson, Bill (Black Swan, 2015)
Whether braving the homicidal motorists of Paris, being robbed by gypsies in Florence, attempting not to order tripe and eyeballs in a German restaurant or window-shopping in the sex shops of the Reeperbahn, Bryson takes in the sights, dissects the culture and illuminates each place and person with his hilariously caustic observations. He even goes to Liechtenstein.